Plasticity of porous NiTi alloys obtained by self-propagating high-temperature synthesis in closed and open gas flow reactors - Marchenko, Ekaterina S.; Yasenchuk, Yuriy F.; Mamazakirov, Oibek R.; Klopotov, Anatoly A.; Baigonakova, Gulsharat A.; Volinsky, Alex A.; Gunter, Sergey V. (Materials and manufacturing processes)
Porous NiTi alloys were obtained by self-propagating high-temperature synthesis (SHS) using layer-bylayer combustion in closed and open gas flow reactors under a protective argon atmosphere. The maximum compressive strain of porous NiTi alloys synthesized in the closed reactor was 34% compared to 7% in the open gas flow reactor. X-ray diffraction, differential scanning calorimetry, scanning electron microscopy, energy dispersive spectroscopy, and optical microscopy showed that the reaction products in the two-phase gas zone of peritectic crystallization are in the form of isolated Ti2Ni crystalline clusters in the TiNi matrix. The ductility and strength of the recrystallized Ti2Ni phase hard dendrites increase the effective stiffness of porous NiTi alloys and decrease the maximum compressive strain. A highly porous NiTi alloy with improved mechanical properties was obtained by the SHS method in a closed reactor.